A Method for Supporting Medical-Interview Trainings Using Wearable Smart Glasses - Mikifumi Shikida; Kunimasa Yagi (Journal of ICT, Design, Engineering and Technological Science, 2017)
This article aims to focus on applying ICT to training in medical schools. We propose a method — using wearable smart glasses — for supporting training in giving medical interviews. Applying this method, the trainer monitors the trainees via a network and sends instructions to individual trainees. Accordingly, it supports the trainer in a manner that eases their burden. Moreover, the trainees can check their current statuses on the display of the smart glasses and get efficient feedback immediately from the trainer As part of medical care, the process of asking patients detailed questions about their symptoms — namely, a medical interview to diagnose a medical problem exactly or to determine the kind of examination of symptoms — is very important. Giving a medical interview successfully depends on the experience of the interviewer. A clinician with a lot of experience can extract the necessary information from outpatients. In response to this state of affairs, clinical lectures have lately been focused on. Especially, training in giving medical interviews has become one of the most important items on the curriculum. This training should be repeated by students so that they can master the technical skill of asking medical interview questions.